An experimental study of heavy mineral segregation under alluvial-flow conditions - Brady, Lawrence L., author; Jobson, Harvey E., author; U.S. Department of the Interior, Geological Survey, publisher (Colorado State University. Libraries, 1972)
Segregation of opaque minerals (mainly ilmenite and magnetite) from the light minerals in a natural sand was observed in a large (61 x 2.44 x 1.22 meters) recirculating water-sediment flume. Bed material (median size 0.286 millimeter) used in the study was taken from the Rio Grande near Bernardo, New Mexico. Opaque heavy minerals (median size 0.144 millimeter) present in the bed material comprised 0.38 percent of the bed material volume. Significant hydraulic variables, and sorting and bedding patterns of the bed material, were observed for four different bed configurations: a flat bed (upper flow regime), a transition bed, and two different dune beds (lower flow regime). Accumulations of opaque heavy minerals were formed as three basic types: 1. thin accumulations of opaque heavy minerals covering small areas that were associated with the upstream or stoss slopes of dunes; 2. accumulations associated with the topset deposits of large dunes and with dunes formed in the transition flow; 3. accumulations associated with the flat-bed condition. The most important factors influencing the type and amount of accumulation of opaque heavy minerals are bed configuration and grain density. Segregation of heavy minerals associated with flat beds occurred mainly at the base of the planar beds, where the most widespread deposit of opaque heavy minerals of the three segregating processes form. The thickest deposits of opaque heavy mineral grains were associated with topset deposits of dune beds, but local conditions must be optimum for thick accumulations to occur. Mineral density is important to segregation because the difference in shear stress necessary to move the light minerals and to move opaque heavy minerals is large. This is shown by means of theoretical considerations of the forces necessary to move grains of two different densities and by means of analysis of the bed material and core samples using a Shields' type criteria for initiation of motion. Sediment size, sorting, and shape were determined for each mineral group from core samples taken from the bed. The sorting of the opaque heavy minerals for the flat bed run was significantly different than that for the other runs.
CER71-72HEJ41.
March 1972.
Open-file report.
Circulating copy deaccessioned 2020.
Keywords: Heavy minerals; Sediment transport -- Experiments